GIMNASTIKANÍŃ DENE TÁRBIYASÍ HÁM SPORT SHEBERLIGIN ASÍRÍW SISTEMASÍNDAǴÍ ORNÍ - Karimov, D. (SCIENCE and SOCIETY, 2022)
The article discusses the goals and objectives of improving the skills of gymnastics. The division of gymnastics classes into groups such as pure exercises, rhythmic gymnastics exercises in accordance with the system of activities that motivate pedagogical tasks is analyzed on the basis of examples. The features and basic tools of gymnastics in improving sportsmanship are also studied in detail.